Making sense of suicide missions - Gambetta, Diego, 1952- (Oxford : Oxford University Press, 2005)
Based on a wealth of original information and research, and containing contributions from internationally distinguished scholars,'Making Sense of Suicide Missions' furthers our understanding of this chilling feature of the contemporary world in radically new and unexpected ways.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Suicide -- Political aspects; Suicide bombings; Kamikaze airplanes